2007
DOI: 10.1111/j.1468-0432.2007.00374.x
|View full text |Cite
|
Sign up to set email alerts
|

The Codex, the Codicil and the Codpiece: Some Thoughts on Diminution and Elaboration in Identity Formation

Abstract: This article is about the way in which the processes of diminution and elaboration can be detected in gendered accounts of identity formation. Firstly, it considers the ways in which power is denied to women through a series of reductions, restrictions and controls, and looks at the ways in which men, in contrast, elaborate their identities via a range of enlargements and extensions. The codex of the title refers to the role of the 'Law', in Kristeva's sense of the term, in authorizing such arrangements. The c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 4 publications
0
49
0
1
Order By: Relevance
“…Advances are needed to expose masculine organization research discourse and the oppressive practice of regulating the text in ways which keep women and their work, the feminine ‘impurity’ and bodily presence, in conformity with the phallogocentric order (Höpfl, , p. 100). Feminist perspectives in organization studies have suggested, as alternatives, writing with ‘dirt’ (Pullen and Rhodes, ) or subversively (Höpfl, ), and expressing the researcher's self‐multiplicity (Pullen, ). I suggest that arts‐based forms can be seen as another alternative to masculine academic writing, in particular arts‐based methods as ‘feminine creation’ with an emphasis on female corporeality and experience in organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Advances are needed to expose masculine organization research discourse and the oppressive practice of regulating the text in ways which keep women and their work, the feminine ‘impurity’ and bodily presence, in conformity with the phallogocentric order (Höpfl, , p. 100). Feminist perspectives in organization studies have suggested, as alternatives, writing with ‘dirt’ (Pullen and Rhodes, ) or subversively (Höpfl, ), and expressing the researcher's self‐multiplicity (Pullen, ). I suggest that arts‐based forms can be seen as another alternative to masculine academic writing, in particular arts‐based methods as ‘feminine creation’ with an emphasis on female corporeality and experience in organizations.…”
Section: Introductionmentioning
confidence: 99%
“…Yet while the work of female scholars who draw on feminist 9 writers is now appearing in major journals (Höpfl, 2000(Höpfl, , 2007Marshall, 2000;Tyler and Cohen, 2009;Kenny 2010;Vachhani, 2012, Fotaki, 2013Ford and Harding, 2008) too often female voices continue to be silenced, discounted and/or misrepresented. This situation is problematic: since writing involves and is concerned with corporeal practices (Pullen, 2006), we need to explore fully what it means to write gendered research from the feminine perspective/body.…”
mentioning
confidence: 99%
“…Höpfl, 2007) -an affront that has begun to be practised in certain narrative approaches. This is not a call for a better understanding of gender on existing theoretical terms, but an attestation to a different kind of research praxis: an embodied writing that works to undermine and expose as a male fantasy those discourses of the truth that dominate organization studies.…”
Section: Organization Studies 35(3)mentioning
confidence: 99%